N-[2-(4-Bromobenzoyl)ethyl]isopropylaminium chloride - Şahi̇n, Ertan; Akkurt, Mehmet; Aydin, Abdullah; Mete, Ebru; Gül, Halise İnci (International Union of Crystallography (IUCr), 2011)
The crystal structure of the title compound, C(12)H(17)BrNO(+)·Cl(-), is stabilized by N-H⋯Cl and C-H⋯O hydrogen bonds, forming a three-dimensional network. The inter-actions framework is completed by C-H⋯π contacts between a methyl-ene group and the benzene ring of a symmetry-related mol-ecule.
Keywords: Crystallography; QD901-999; Organic Papers; 3. Good health